HIV testing and associated factors among men (15-64 years) in Eastern Africa: a multilevel analysis using the recent demographic and health survey - Dagnew Getnet Adugna; Misganaw Gebrie Worku (BMC, 2022)
Abstract Background Despite significant efforts made to prevent human immunodeficiency virus (HIV) transmission, its testing coverage among men is still low and remains a major concern in low-income countries, particularly in East Africa. Therefore, this study aimed to determine the prevalence and associated factors of HIV testing among men in Eastern Africa. Methods We analyzed secondary data using Demographic and Health Surveys (DHS) drawn from Eastern African countries. Besides, we merged DHS data from eleven Eastern African countries. In this study, we included secondary data from 113, 270 men aged 15-64 years. The outcome variable of this study was "ever been tested for HIV". Bivariable and multivariable multi-level logistic regression analyses were employed. In the bivariable analysis, variables having a P-value of less than 0.2 were selected for multivariable analysis. Lastly, variables with a P-value of < 0.05 in the multivariable analysis were declared as a significant factor associated with HIV testing and the adjusted odds ratio (AOR) with the 95% confidence interval (CI) were computed to determine the strength and direction of the association. Results The overall prevalence of HIV testing among men in eastern Africa was 60.5% (95% CI: 60.2, 60.7%). In the multivariable multilevel analysis; participant's older age, being married, increased poverty, HIV knowledge, risky sexual behavior, and being covered by health insurance were positively associated with HIV testing coverage among men. However, men with higher community illiteracy levels, residing in rural settings, age at first sex ≥20 years, and higher stigmatized attitudes towards HIV/AIDS had lower odds of being tested for HIV. Conclusion The overall prevalence of HIV testing among men in eastern Africa was relatively higher than the previous studies. The study revealed that age, marital status, residence, age at first sex, community poverty level, community illiteracy level, HIV knowledge, HIV stigma indicator, risky sexual behavior, and health insurance were significantly associated with HIV testing coverage among men. Therefore, all the concerned stakeholders need to develop an integrated strategic plan through providing special attention to the factors that affect the uptake of HIV testing to raise awareness about the importance of HIV testing and to prevent HIV/AIDS transmission.